Laryngeal Preservation Strategies in Locally Advanced Laryngeal and Hypopharyngeal Cancers - Argiris, Athanassios; Lefebvre, Jean Louis (Frontiers in Oncology, 2019)
For long, the treatment of locoregionally advanced laryngeal and hypopharyngeal squamous cell cancers (SCC) consisted of either total laryngectomy (TL) or definitive radiotherapy (RT). The development of induction cisplatin plus 5-fluorouracil (PF) and the correlation between chemosensitivity and radiosensitivity in previously untreated patients opened a new era of treatment aiming at laryngeal preservation (LP). The fundamental concept was to employ induction PF in order to select patients for subsequent treatment with either TL or RT according to tumor response to PF. The first two trials (VALGSG for laryngeal SCC and EORTC 24891 for hypopharyngeal SCC) concluded that such an approach could preserve nearly 60% of larynx without deleterious impact on survival. The EORTC 24954 trial compared 4 cycles of induction PF followed by RT in good responders vs. alternating PF-RT in laryngeal and hypopharyngeal SCC. There was no significant difference in 5-year overall survival with a functional larynx between the two arms (31 vs. 35%). The GORTEC 2000-01 trial compared induction PF to induction PF plus docetaxel (TPF) both followed by RT in good responders in larynx and hypopharynx SCC. The 5-year LP was significantly higher in the TPF arm (60 vs. 39%) but without a difference in survival. The RTOG 91-11 trial compared induction PF followed by RT in good responders vs. concurrent chemoradiotherapy (chemo-RT) vs. RT alone in laryngeal SCC. There was no significant difference in 5-year laryngectomy-free survival between the patients treated with induction chemotherapy (44%) vs. those treated with chemo-RT (47%), both being superior to RT alone (34%). At 5 years, LP was superior with chemo-RT: 84 vs. 71% with induction PF. Two phase II trials explored the role of cetuximab (E) in LP in laryngeal and hypopharyngeal SCC. The TREMPLIN trial compared RT+E or chemo-RT (RT + P) after TPF. The DeLOS-II trial compared TPE followed by RT+E vs. TP followed by RT. However, these trials failed to indicate an advantage for the incorporation of E in the treatment paradigm. To date, two approaches for LP have been validated: induction TPF followed by RT for laryngeal and hypopharyngeal SCC and concurrent chemo-RT for laryngeal SCC. An ongoing trial (SALTORL) is comparing these two approaches, induction TPF and chemo-RT, in laryngeal/ hypopharyngeal SCC.